Problematic internet usage among high school students and the relevant factors - Rukuye Aylaz; Gülsen Güneş; Yurdagül Günaydın; Mustafa Kocaer; Erkan Pehlivan (Turkish Society of Public Health Specialists, 2015)
Objective: In this study we studied the problematic internet usage among high school students and the relevant factors. Methods: This cross sectional study was done in March 2010. A questionnaire was filled by 435 students from 6 different classes. A personal information form and a problematic internet usage scale were developed by the authors were used. Number, percentage, average and t-test for the independent groups were used for the statistical analyses. Results: 53.8% of the students is male and 46.2% of them is female. 74.4%   reported that they had a computer at home, 63.9% reported that they had used the internet for more than 2 years. 42.6% complained about redness in their eyes and 28.3% complained about aches in the neck muscles. According to the problematic internet usage scale total point for boys is 131.16±25.0 and for girls it is 137.74±21.6 (p=0.012). Conclusion: According to this study a statistically important relationship between gender and problematic internet use has been shown. Female students, students who are smoking and students who have sleeping problems, reported problematic internet use more than the others. Keywords: Problematic internet use, adolescent, health.